2014
DOI: 10.1111/bjd.12715
|View full text |Cite
|
Sign up to set email alerts
|

High levels of type VII collagen expression in recessive dystrophic epidermolysis bullosa cutaneous squamous cell carcinoma keratinocytes increases PI3K and MAPK signalling, cell migration and invasion

Abstract: Our data suggest caution when formulating strategies where delivery of type VII collagen is likely to exceed levels seen under normal physiological conditions in a patient group with a higher inherent risk of developing skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Collagen synthesis and degradation affected by inflammation may contribute to changes in cell spreading and migration and, therefore, regeneration and disease progression. [84][85][86] Epithelial cell and epithelial stem cell/progenitor cell behavior in chronic inflammation is poorly characterized. The stem cell transcription factors array showed a significant decrease in the majority of LG epithelial stem/progenitor cell markers, such as Pax6, Sox6, Sox9, Six2, Klf4, and Notch2, that control LG development and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen synthesis and degradation affected by inflammation may contribute to changes in cell spreading and migration and, therefore, regeneration and disease progression. [84][85][86] Epithelial cell and epithelial stem cell/progenitor cell behavior in chronic inflammation is poorly characterized. The stem cell transcription factors array showed a significant decrease in the majority of LG epithelial stem/progenitor cell markers, such as Pax6, Sox6, Sox9, Six2, Klf4, and Notch2, that control LG development and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is characterized by skin and mucosal fragility due to a decrease in Col7 formation (the main component of anchoring fibrils) which leads to blister formation and chronic skin traumatisms (risk factor for SCC) [71]. Considering the fact that patients with dominant dystrophic epidermolysis bullosa (1 normal COL7A1 allele which means 50% normal Col 7 formation) develop SCC less than RDEB patients [71], scientists are trying to increase Col7 formation through divers methods (gene, protein, and cell therapy), but it was observed that high levels of Col7 are correlated with an important activation of the phosphoinositide 3-kinase pathway that leads to an increased invasion in SCC keratinocytes; therefore this kind of therapies should be applied with caution [116]. Matrix metalloproteinases are molecules implicated in maintaining homeostasis of many tissues including skin, by proteolysis of extracellular matrix.…”
Section: Proteic and Other Potential Biomarkers Of Squamous Cell Cmentioning
confidence: 99%
“…The aggressive nature of RDEB-SCC, including enhanced migration and invasion, has been confirmed by in vitro experiments using SCC cell lines with siRNA-induced COL7 depletion. 97 The cellular phenotype may vary depending on COL7 expression levels, 98 demonstrated when overexpression of COL7 in RDEB cells exceeds the physiological level of the protein. 98 Terminal differentiation of RDEB-SCC cells is suppressed in vivo and in xenograft models.…”
Section: Col7 In Wound Healing and Carcinogenesis Of Keratinocytesmentioning
confidence: 99%
“…97 The cellular phenotype may vary depending on COL7 expression levels, 98 demonstrated when overexpression of COL7 in RDEB cells exceeds the physiological level of the protein. 98 Terminal differentiation of RDEB-SCC cells is suppressed in vivo and in xenograft models. 97,99 In studies in which dermal components were also assessed, dermal tissue stiffening due to increased extracellular matrix production 57 and angiogenesis 99 have been shown to result from COL7 depletion in epidermal keratinocytes and to subsequently facilitate the development and aggressive nature of RDEB-SCC.…”
Section: Col7 In Wound Healing and Carcinogenesis Of Keratinocytesmentioning
confidence: 99%